Formative process in Cesar Vallejo’s poetic thinking: Romanticism in Spanish poetry (1915): El Romanticismo en la poesía castellana (1915) - Flores Heredia, Gladys (2019)
This paper analyzes and interprets the content and formal elements in Cesar Vallejo’s thesis: Romanticism in Spanish poetry (1915). It is suggested that the thesis is read as the scenery of the exposure of ideas where Vallejo not only expresses his systematic knowledge about the history of romantic poetry as well as his comprehension of the logic that encourages the critical discourse and his relationship with literature. This involves reading the thesis in a way that provides insight into that Vallejo, who wrote Los heraldos negros (‘The Black Heralds’, 1919), is an author that doesn’t ignore the dialectic that goes through the different literary manifestations, historic and social series. On the contrary, the thesis allows us to appreciate that Vallejo has understood that the aesthetic to come is something that requires originality in the historicsensibility and the poetic language.